Co-Treatments of Gardeniae Fructus and Silymarin Ameliorates Excessive Oxidative Stress-Driven Liver Fibrosis by Regulation of Hepatic Sirtuin1 Activities Using Thioacetamide-Induced Mice Model - Jin A Lee; Mi-Rae Shin; JeongWon Choi; MinJu Kim; Hae-Jin Park; Seong-Soo Roh (MDPI AG, 2022)
Gardeniae Fructus (GF, the dried ripe fruits of Gardenia jasminoides Ellis) has traditionally been used to treat various diseases in East Asian countries, such as liver disease. Silymarin is a well-known medicine used to treat numerous liver diseases globally. The present study was purposed to evaluate the synergistic effects of GF and silymarin on the thioacetamide (TAA)-induced liver fibrosis of a mouse model. Mice were orally administered with distilled water, GF (100 mg/kg, GF 100), silymarin (100 mg/kg, Sily 100), and GF and silymarin mixtures (50 and 100 mg/kg, GS 50 and 100). The GS group showed remarkable amelioration of liver injury in the serum levels and histopathology by observing the inflamed cell infiltrations and decreases in necrotic bodies through the liver tissue. TAA caused liver tissue oxidation, which was evidenced by the abnormal statuses of lipid peroxidation and deteriorations in the total glutathione in the hepatic protein levels; moreover, the immunohistochemistry supported the increases in the positive signals against 4-hydroxyneal and 8-OHdG through the liver tissue. These alterations corresponded well to hepatic inflammation by an increase in F4/80 positive cells and increases in pro-inflammatory cytokines in the hepatic protein levels; however, administration with GS, especially the high dose group, not only remarkably reduced oxidative stress and DNA damage in the liver cells but also considerably diminished pro-inflammatory cytokines, which were driven by Kupffer cell activations, as compared with each of the single treatment groups. The pharmacological properties of GS prolonged liver fibrosis by the amelioration of hepatic stellate cells' (HSCs') activation that is dominantly expressed by huge extracellular matrix (ECM) molecules including α-smooth muscle actin, and collagen type1 and 3, respectively. We further figured out that GS ameliorated HSCs activated by the regulation of Sirtuin 1 (Sirt1) activities in the hepatic protein levels, and this finding excellently reenacted the transforming growth factor-β-treated LX-2-cells-induced cell death signals depending on the Sirt1 activities. Future studies need to reveal the pharmacological roles of GS on the specific cell types during the liver fibrosis condition.